2014
DOI: 10.1016/j.jconrel.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Injectable, self-gelling, biodegradable, and immunomodulatory DNA hydrogel for antigen delivery

Abstract: DNA nanotechnology-based nanosystems and macrosystems have attracted much attention in the biomedical research field. The nature of DNA endows these systems with biodegradable, biocompatible, and immunomodulatory properties. Here, we present an injectable hydrogel system that consists only of chemically synthesized short DNA strands, water, and salts. Several preparations of polypod-like structured DNA, or polypodna, were designed, including tri-, tetra-, penta- and hexapodna, as the building blocks of self-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
127
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 36 publications
3
127
0
Order By: Relevance
“…[ 21 ] GpC DNA hydrogel was prepared by replacing CpG sequences in the ODNs of the CpG DNA hydrogel with GpC sequences, and was used as a control. Complex formation of OVA or ED-OVAs with DNA was examined by PAGE.…”
Section: Cationized Ova Formed a Complex With Dna And Was Gradually Rmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] GpC DNA hydrogel was prepared by replacing CpG sequences in the ODNs of the CpG DNA hydrogel with GpC sequences, and was used as a control. Complex formation of OVA or ED-OVAs with DNA was examined by PAGE.…”
Section: Cationized Ova Formed a Complex With Dna And Was Gradually Rmentioning
confidence: 99%
“…[ 21 ] However, OVA was released from the hydrogel with a half-life of about 2.5 h, and this rapid release reduced the potency of the injectable CpG DNA hydrogel as a controlled antigen delivery system with adjuvant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has also been reported that increasing the concentration of these polypod-like CpG ODNs, increasing the salt concentration in the solvent, or forcing the polypodlike CpG ODNs to self-associate with other DNA results in the formation of a hydrogel by the CpG ODNs. 80 In the self-association process where the polypod-like CpG ODNs are forced to undergo self-association with other DNA, it is possible to incorporate antigens into the self-gelling DNA. Ishii-Mizuno et al 81 prepared a CpG ODN hydrogel, containing the Japanese cedar pollen allergen Cryj1, through self-gelling of two types of hexapod-like CpG ODNs with a 5′-end complementary sequence.…”
mentioning
confidence: 99%
“…Moreover, in mice injected with a CpG ODN hydrogel loaded with the model antigen ovalbumin (OVA), the OVA-specific CTL was activated. 80 Thus, the CpG ODN hydrogel could be applied to the treatment of infectious diseases and to cancer immunotherapy.…”
mentioning
confidence: 99%
“…55 For the crystal structure of CaP prepared for ds CpG-B72-PD complexation, we detected a band attributed to the CO 3 2− group at 862 cm −1 in the FTIR spectrum. The band for the CO 3 2− group of hydroxyapatite generally appears around 1,400-1,600 cm −1 ( Figure S9), but we did not observe this band in our CaP.…”
Section: Discussionmentioning
confidence: 90%